The beginnings of psychologist profession in Argentina: science, institutional context and society - Klappenbach, Hugo Alberto Arturo (2023)
The chapter begins analyzing the first developments in Psychology at the end of 19th Century and beginnings of 20th Century. In those years, Psychology appeared to be a knowledge able to help professions like medicine, pedagogy or legal profession. Then, the chapter exhibits a very import shift happened at the middle of 20th century when began some undergraduate programs in the field of psychology. Usually, such programs were not labeled in Psychology, but in Psychotechnichs and Professional Guidance. The chapter analyzes the scientific orientation of such programs, based on French psychology, as well as the institutional and political factors promoting psychological programs. Last, the chapter exposes the re-orientation of psychology education at universities since the second half of the 60s, when psychology became synonymous of psychoanalysis. On the one hand, it analyzes the institutional and political background for the constitution of the profession of psychologist. On the other one, it exhibits the main ways supporting psychologist psychoanalytically biased profession: epistemological and theoretical approaches within science and psychology education, clinical practices in public institutions, and a virtual repudiation of alternative models of knowing and practicing.